The Moderating Effect of Earnings Management and Dividend Policy on Relationship Between Corporate Governance and Institutional Foreign Ownership - Arin Pranesti; Indra Wijaya Kusuma (Universitas Muhammadiyah Malang, 2021)
This study aims to examine the effect of corporate governance on institutional foreign ownership with earnings management and dividend policy as moderating variable. Previous research tends to be done in developed countries. In addition, prior research that examined the relationship between corporate governance and foreign institutional ownership is relatively inconclusive. Kim (2015) concluded that although some prior studies have found a correlation between corporate governance and institutional foreign ownership, there has been no research that explains the causality relationship. This study uses a corporate governance index that formed through the results of factor analysis test. The results of statistical tests indicate that corporate governance can be used as a good signal to pursue external parties that imply the company that has a good oversight mechanism. Interaction testing results between earnings management and corporate governance imply that foreign institutional investors tend to rely on corporate governance signals. In contrast, the interplay of dividend and corporate governance policies shows significant results. Therefore, it can be concluded that companies that have good corporate governance and dividend policies can reduce the conflict of interest between agents and principals tend to attract foreign institutional investors to invest in the company